(untitled) (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2025)
The bi-centennial history of the Monroe Doctrine is a history of adaptations, transformations, and appropriations. The first part of the essay discusses three major turning points. The text of 1823 envisioned the Western Hemisphere as an “imagined community” of American republics based on a shared, if somewhat elusive, identity, while the 1904 corollary transformed it in a US-enforced security system. Finally, its deployment within the inter-American system along the 20th century led to creation of a US-led “international empire”. The second part discusses the Second International Conference of the American States (1901-1902), an often-overlooked episode in the history of the inter-American system that in fact paved the way for international empire as the type of imperial formation operating in the Western hemisphere across the 20th century.